Performance of visual stimuli in the diagnosis of ASD by Eye Tracking: A Systematic Review - Martínez-Lorca, Manuela; Gómez Fernández, Diego (Revista de Investigación en Logopedia, 2023)
Eye-tracking is defined as a diagnostic tool that aims to study gaze behavior through eye scanning. This system has been used with children with ASD, and that is why by means of the eye-tracking system, the evaluators can observe how the person tracks their eyes, how they distribute their gaze, and see precisely how they and see precisely the activity in terms of their eye movements. The main objective of this review has been to analyze the performance of visual stimuli in the diagnosis of ASD by eye tracking method. In order to carry out this review different sources of information were established, such as databases, including PubMed, Science Direct and Scopus, as well as other platforms such as Research Gate. After applying exclusion and inclusion criteria, 22 articles were selected. These articles describe research describing experiments with unifactorial designs, factorial experimental and quasi-experimental designs. All the experiments had a control group and a case group, composed of a sample of normotypically developing participants and a group composed of a sample of participants with ASD. Discussion: an analysis of the performance of visual stimuli in the diagnosis by means of the eye tracking system in the diagnostic using the eye tracking system on the basis of the characteristics of the stimulus used in the diagnosis, the main results found and finally the main conclusions found. Conclusions: social stimuli and confrontational stimuli will be effective in establishing an accurate diagnosis of ASD. To establish an accurate diagnosis of presenting ASD since they allow to screen both groups and to establish an early risk of ASD.